New use of an old drug: mechanism of oseltamivir phosphate inhibiting liver cancer through regulation of lipophagy via NEU1 - Chen, Yuyu; Han, Peiyu; Zhu, Haixia; Zhang, Wenchao; Ma, Xiaoyu; He, Yiting; Chen, Hetian; He, Weiwei; Wu, Yu; Ge, Yuqiu (Frontiers in Pharmacology, 2025)
BackgroundNeuraminidase-1 (NEU1) is an enzyme that breaks down sialic acids on glycoproteins and glycolipids. Aberrant expression of NEU1 has been linked to the progression of numerous malignancies, including liver cancer. Oseltamivir phosphate (OP) is a drug used to treat and prevent influenza, which specifically inhibits NEU1. However, the molecular mechanisms of NEU1 in liver cancer and the potential therapeutic effects of OP remain largely unclear.MethodsNEU1 expression in liver cancer was evaluated using public databases and validated in our samples. CRISPR/Cas9, CCK-8 assay, transwell assays, oil red O staining, RNA-sequencing, immunofluorescence and co-immunoprecipitation (Co-IP) and in vivo experiments were used to investigate the biological function of NEU1 and the therapeutic effect of OP in liver cancer.ResultsWe demonstrated that NEU1 expression was significantly elevated in liver cancer cells and tumor tissues. Patients with liver cancer exhibiting high levels of NEU1 expression tended to have a less favorable prognosis. NEU1 knockdown inhibited liver cancer cells proliferation, invasion and migration. Subsequent experiments demonstrated that NEU1 knockdown reduced lipid accumulation through promoting perilipin 2 (PLIN2)-mediated lipophagy. Notably, OP (NEU1 inhibitor), promoted lipophagy, thereby inhibiting liver cancer proliferation and tumorigenesis. Moreover, liver cancer cells were more sensitive to OP compared to other chemotherapeutics, like 5-fluorouracil and gemcitabine, with a reduced drug resistance.ConclusionOP inhibits liver cancer progression by targeting NEU1 and inducing lipophagy through the suppression of PLIN2. Our findings provide new directions on the role of NEU1 in liver cancer and offer latent strategies to address the chemotherapy-induced drug resistance.